2017
DOI: 10.1002/mus.25968
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal quantitative examination of nerve function in colorectal cancer patients prior to chemotherapy

Abstract: The present study has established a low likelihood of significant distal symmetrical polyneuropathy in colorectal cancer patients before initiation of chemotherapy. Muscle Nerve 57: 615-621, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Motor dysfunction has been shown in a small-scale study, where decreased superexcitability of motor axons was reported [41]. Furthermore, a neurophysiological study in children receiving vincristine showed impaired myotatic reflexes and motor neural impairment [42] and a larger study in oxaliplatin-treated patients found no nerve dysfunction before the initiation of chemotherapy [43] while others studies (ie. ref.…”
Section: Discussionmentioning
confidence: 99%
“…Motor dysfunction has been shown in a small-scale study, where decreased superexcitability of motor axons was reported [41]. Furthermore, a neurophysiological study in children receiving vincristine showed impaired myotatic reflexes and motor neural impairment [42] and a larger study in oxaliplatin-treated patients found no nerve dysfunction before the initiation of chemotherapy [43] while others studies (ie. ref.…”
Section: Discussionmentioning
confidence: 99%